Fatigue Across the Lifespan in Men and Women: State vs. Trait - Wylie, Glenn R.; Pra Sisto, Amanda J.; Genova, Helen M.; DeLuca, John (Frontiers in Human Neuroscience, 2022)
Objective: Fatigue is commonly thought to worsen with age, but the literature is mixed: some studies show that older individuals experience more fatigue, others report the reverse. Some inconsistencies in the literature may be related to gender differences in fatigue while others may be due to differences in the instruments used to study fatigue, since the correlation between state (in the moment) and trait (over an extended period of time) measures of fatigue has been shown to be weak. The purpose of the current study was to examine both state and trait fatigue across age and gender using neuroimaging and self-report data. Methods: We investigated the effects of age and gender in 43 healthy individuals on self-reported fatigue using the Modified Fatigue Impact Scale (MFIS), a measure of trait fatigue. We also conducted fMRI scans on these individuals and collected self-reported measures of state fatigue using the visual analog scale of fatigue (VAS-F) during a fatiguing task. Results: There was no correlation between age and total MFIS score (trait fatigue) (r=-.029, p=0.873), nor was there an effect of gender (F(1,31)= -.11, p= 0.92). However, for state fatigue, increasing age was associated with less fatigue (F(1,35)=9.19, p < 0.01, coefficient = -0.4). In the neuroimaging data, age interacted with VAS-F in the middle frontal gyrus. In younger individuals (20-32), more activation was associated with less fatigue, for individuals aged 33-48 there was no relationship, and for older individuals (55+) more activation was associated with more fatigue. Gender also interacted with VAS-F in several areas including the orbital, middle and inferior frontal gyri. For women, more activation was associated with less fatigue while for men, more activation was associated with more fatigue. Conclusions: Older individuals reported less fatigue during task performance (state measures). The neuroimaging data indicate that the role of middle frontal areas change across age: younger individuals may use these areas to combat fatigue, but this is not the case with older individuals. Moreover, these results may suggest greater resilience in females than males when faced with a fatiguing task.